2021
DOI: 10.1182/blood.2020010536
|View full text |Cite
|
Sign up to set email alerts
|

The impact of increasing karyotypic complexity and evolution on survival in patients with CLL treated with ibrutinib

Abstract: Complex karyotype defined as ≥3 cytogenetic abnormalities is prognostic of survival in patients treated with ibrutinib or venetoclax in relapsed/refractory (RR) chronic lymphocytic leukemia (CLL). Recent studies re-evaluating this dichotomous variable have shown that higher numbers of cytogenetic abnormalities (i.e. ≥5) have a worse overall survival in patients treated with chemoimmunotherapy. We sought to determine if increasing karyotypic complexity, treated as a continuous variable, was prognostic of surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 40 publications
2
41
0
1
Order By: Relevance
“…Nevertheless, the low number of high-CK (5%) at least at front-line treatment underscores the need for large population-studies, since it will be difficult to recruit the required number of patients with high-CK in the context of a clinical trial in order to reach statistical significance. Following this approach, it was recently reported that increasing cytogenetic complexity was an independent predictor of shorter PFS [HR1.07 (95% CI 1.04–1.10), p <0.0001] and overall survival [HR 1.09 (95% CI 1.05–1.12), p <0.0001] for patients treated with ibrutinib ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the low number of high-CK (5%) at least at front-line treatment underscores the need for large population-studies, since it will be difficult to recruit the required number of patients with high-CK in the context of a clinical trial in order to reach statistical significance. Following this approach, it was recently reported that increasing cytogenetic complexity was an independent predictor of shorter PFS [HR1.07 (95% CI 1.04–1.10), p <0.0001] and overall survival [HR 1.09 (95% CI 1.05–1.12), p <0.0001] for patients treated with ibrutinib ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the sequenced capture genes identified mutations in 35 patients (Figure 3). Thirty nine TP53 mutations were detected in 16 patients (16%) with a median of 1 mutation per patient (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and a median allele frequency of 4% (1-90). The patient who had 15 TP53 mutations did not display CNA for this gene.…”
Section: Oncogene Variants Analysismentioning
confidence: 99%
“…55 However, when considering predicting PFS, the model reported by Ahn et al, which included del(17p)/TP53 mutations, was more accurate than the BALL score. 56 More recently, in an attempt to better define clinical implications of karyotype complexity in the setting of patients treated with ibrutinib, Kittai et al 57 analyzed a patient cohort including both treatment naïve (TN) or relapsed/refractory (R/R) CLL patients treated at Ohio State University. In a multivariable analysis, increasing karyotypic complexity was an independent predictor of shorter PFS and OS.…”
Section: Prognostic Models In the Era Of Targeted Agentsmentioning
confidence: 99%
“…Importantly, this study demonstrated for the first time that karyotypic complexity, which acts as a continuous variable, should be incorporated in future models predicting clinical outcomes of CLL patients, especially if treated with BTK inhibitors. 57 In the era of targeted therapy, the development of prognostic models is still an ongoing process and will undoubtedly lead us to new questions that will need to be solved. Another area for further study relates to using these models in the context of combination therapy versus monotherapy.…”
Section: Prognostic Models In the Era Of Targeted Agentsmentioning
confidence: 99%